Bivalence Mn5O8 with hydroxylated interphase for high-voltage aqueous sodium-ion storage - Xiaoqiang Shan (Nature Portfolio, 2016)
Rechargeable aqueous electrochemical energy storage is a promising technology but suffers from a narrow potential window. Here the authors report a surface hydroxylated Mn5O8pseudocapacitor electrode with bivalence structure that expands the potential window to deliver high energy and power performance.